Peer effects in collaborative content generation: The evidence from German Wikipedia - Olga Slivko (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
On Wikipedia, the largest online encyclopedia, editors who contribute to the same articles and exchange comments on articles' talk pages work in collaborative manner engaging in communication about their work. Thus they can be considered as peers who are likely to influence each other. In this article, I examine whether the activity of these peers, measured by the average amount of peer contributions or by the number of peers, yields spillovers to the amount of individual contributions. The partially overlapping group structure allows to identify peer effects and to use the number of the indirect peers as an instrument for the activity and the number of direct peers. The results show that, while controlling for observable editor and peer characteristics, an increase in the monthly average peer contribution by 1 per cent increases the amount of individual monthly contributions to Wikipedia (among individuals that contribute to Wikipedia every month) by about 0.44 per cent. Similarly, spillovers coming from the number of peers yield a positive effect of 0.17 per cent per article to 0.05 per cent for overall monthly contributions to Wikipedia.
urn:nbn:de:bsz:180-madoc-375366; More recent version: http://hdl.handle.net/10419/110597
Keywords: I23; J31; Z13; 330; peer effects; user-generated content; Wikipedia; network of editors; direct and indirect peers